Effects of Process Parameters during Forming of Glass Reinforced-pp based Sandwich Structure - Sivakumar, Dhar Malingam; Subramonian, Sivarao; Mohd Zulkefli, Selamat; Radzai, Said (American-Eurasian Network for Scientific Information, 2014)
The concern about the environmental impact of emissions from automobiles has been a strong move to use lightweight materials for automotive applications. Glass reinforced polypropylene sandwich structure with aluminum skin is 30% lighter than monolithic aluminum. Objective: To study the effects of process parameters during forming of sandwich structure. Results: Strain experienced by the sandwich structure is affected by binder force, stiffness of the composite and glue state. Conclusion: Glass reinforced-PP sandwich structure can be stamp formed and has potential to replace monolithic aluminium.